Estimation the Correlation between Heavy Metals and Oxidative Stress in People Living Near Incineration in Al-Nasr City in Thi-qar Governorate: Estimasi Korelasi antara Logam Berat dan Stres Oksidatif pada Orang yang Tinggal di Dekat Insinerasi di Kota Al-Nasr di Kegubernuran Thi-qar - Yousif, Abdullah Fakhir (Indonesian Journal on Health Science and Medicine, 2024)
Abstract. Background: The current study is a prospective research. Some laboratory tests were done on people living near incineration in Al-Nasr city in thi-qar governorate. This scientific study has its goal as providing social benefits through supporting and augmenting the efforts of Environmental Authority in their work of organizing and monitoring waste disposal processes, with due consideration to the health status of these individuals to help decrease the incidence of waste burning besides finding safe solutions for waste disposal. Methods: The samples were collected from people living near incineration in Al-Nasr city in Thi-Qar governorate. Seventy five samples of blood obtained from subjects residing near incineration, and seventy five samples also obtained from normal individuals as a control group, subject's age ranged between (20-60) years, during the period from October 2022 up to April 2023. Serum levels were assayed for lead (Pb), cadmium (Cd), zinc (Zn), malondialdehyde (MDA), Glutathione (GSH) and albumin (Alb). Results: A highly significant increase in serum Pb, serum Cd, serum Zn, and serum MDA in people living near incineration as compared to the control group was observed. A significant decrease in serum GSH, and serum Alb in people living near incineration as compared to the controls group was found. The study reported a positive correlation between Pb and (Cd, Zn, MDA) while it reported a negative correlation between Pb and (GSH, Alb). Highlights: Prospective study on health impacts of incineration in Al-Nasr city. Blood tests on 75 residents, 75 controls; analyzed Pb, Cd, Zn, MDA, GSH, Alb. Increased Pb, Cd, Zn, MDA; decreased GSH, Alb; correlations observed. Keywords: Oxidative stress, Lead, Cadmium, Zinc, Glutathione, Albumin